Two Greek rhetorical treatises from the Roman Empire : introduction, text, and translation of the Arts of rhetoric, attributed to Anonymous Seguerianus and to Apsines of Gadara - Dilts, Mervin R.; Kennedy, George A. 1928-; Anonymus Seguerianus, active 3rd century.; Apsines, of Gadara, active 3rd century. (Mnemosyne, Supplements, 1997)
A revised Greek Text (the first in a century) and English translation (the first in any modern language) of the Art of Political Speech by a writer known as the Anonymous Seguerianus (ca. A.D. 200) and the Art of Rhetoric of Apsines of Gadara (ca. A.D. 230), with introduction, notes, and indices. These works provide evidence of how rhetoric was taught in Greek in the early centuries of the Roman Empire and show the continued development of an Aristotelian tradition before acceptance of the reorganization of the subject by Hermogenes. They complement each other in that the Anonymous was especially interested in debates about rhetorical theory, while Apsines' primary interest was in analysis of speeches of Demosthenes and other orators and in teaching declamation.